Comprehensive evaluation of 20 pomegranate (Punica granatum L.) cultivars in China - Yan-hui CHEN; Hui-fang GAO; Sa WANG; Xian-yan LIU; Qing-xia HU; Zai-hai JIAN; Ran WAN; Jin-hui SONG; Jiang-li SHI (Journal of Integrative Agriculture)
Recent investigations on pomegranate products have significantly increased and successfully drawn consumers’ attention to nutritional and medicinal values, promoting the pomegranate industry's development worldwide. However, little information on pomegranates grown in China is available. Morphological and chemical characterizations of fruits and arils from 20 pomegranate cultivars in six regions of China were investigated. Combined with overall scores by principal component analysis, ‘Yushiliu No. 1’, ‘Taishanhong No. 2’, ‘Tunisia’ and ‘Mollar’ were promising cultivars, and Chinese researchers bred the first two. It was surprising that ‘Mollar’ had bigger fruit size and more aril moisture grown in China than in Spain. Cultivars with higher anthocyanin content in arils were ‘Turkey’, ‘Moyu’ and ‘Red Angel’, which might be used as the source of natural red food colourants. While red husk ‘Hongruyi’ and ‘Hongshuangxi’ with higher vitamin C, aril moisture and lower titratable acid in arils, might also be promising cultivars for further various utilization. Furthermore, the comparison of ‘Tunisia’ fruits from four regions revealed that cultivation locations had more influence on fruit traits than genotypes. Maturity index classification was established for Chinese pomegranate cultivars. Therefore, the results would provide a valuable guide for agricultural cultivation, industrial utilization, and breeding.